Epoxy-anhydride vitrimers: Reprocessability via facile transesterification - B. Satheesh Kumar; Temina Mary Robert; K.R. Roshith; Dona Mathew; K.S. Santhosh Kumar (Next Materials)
Vitrimers represent a fascinating class of polymeric materials that exhibit both thermoset and thermoplastic behavior. These materials can be reshaped like thermoplastics while maintaining the robust, crosslinked structure characteristic of thermosets. For most vitrimers, the presence of a catalyst and/or prolonged heating at elevated temperatures are essential for stress relaxation, reprocessability, and the retention of properties. Due to their exceptional mechanical properties, which combine the durability of thermosets with the reprocessability of thermoplastics, vitrimers are anticipated to replace conventional thermosets in a wide range of applications, including aerospace and electronics. In this study, we report on the reprocessability characteristics of a simple epoxy-anhydride composition containing varying amounts of the transesterification catalyst zinc acetylacetonate hydrate. Among the various compositions studied, it was observed that those containing higher catalyst concentrations (15 wt% or more) demonstrated the ability to be reprocessed. Reprocessability can be achieved by placing the broken specimens in contact at a temperature of either 150 °C for 1 hour, 180 °C for 10–15 minutes, or 190 °C for 7–8 minutes, under a contact pressure of 0.5–1 ksc in a hydraulic press. The optimized composition that exhibited the best reprocessability and favorable mechanical properties is the one with a 15 wt% catalyst concentration (EA-15), as confirmed by stress relaxation and sensitivity studies. EA-15 showed improved mechanical properties during reprocessing, with the initial storage modulus and glass transition temperature (Tg) recorded at 1036 MPa and 99 °C, respectively, which increased to 1106 MPa and 109 °C after five reprocessing cycles. Additionally, we demonstrated the reprocessability and reshaping capabilities at the composite level, allowing the same composite material to be utilized multiple times across various profiles and applications. This approach could save time and energy, reduce material waste, and promote sustainability in conventional epoxy composite materials.